2019
DOI: 10.4103/jfmpc.jfmpc_777_19
|View full text |Cite
|
Sign up to set email alerts
|

Study of association of serum uric acid with albuminuria and carotid atherosclerosis in type 2 diabetes mellitus patients

Abstract: Introduction:Type 2 diabetes mellitus is a heterogeneous group of metabolic disorders of disturbance of carbohydrate, fat, and protein metabolism causing macrovascular (like coronary artery disease) and microvascular (kidney damage) complications. Microalbuminuria is the first manifestation of injury to glomerular filtration barrier and carotid intima-media thickness (IMT) of common carotid artery serves as an excellent marker for early lesion of atherosclerosis.Method:A cross-sectional observational study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, this investigation assessed the roles of AS-IV in pancreatic β -cells by employing different concentrations of AS-IV (12.5, 25, 50, 10, and 200 μ mol/l) to stimulate Min6 cells for 24 h. Firstly, the data showed that AS-IV had no cytotoxic effect on pancreatic β -cells. Based on previous studies, excess UA may induce insulin resistance and pancreatic β -cell injury, which was associated with the progression of T2D [ 7 13 ]. Lv et al revealed that high serum UA may increase the risk of T2D [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this investigation assessed the roles of AS-IV in pancreatic β -cells by employing different concentrations of AS-IV (12.5, 25, 50, 10, and 200 μ mol/l) to stimulate Min6 cells for 24 h. Firstly, the data showed that AS-IV had no cytotoxic effect on pancreatic β -cells. Based on previous studies, excess UA may induce insulin resistance and pancreatic β -cell injury, which was associated with the progression of T2D [ 7 13 ]. Lv et al revealed that high serum UA may increase the risk of T2D [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, protecting pancreatic β -cell functions may be an approach for T2D development and therapy. Based on several reports, uric acid (UA) level is associated with β -cell functions, insulin secretion, and the risk of T2D [ 7 10 ]. Several studies also revealed that increased UA could abduct insulin resistance and inhibit pancreatic β -cell survival and insulin product [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%